Analisis Kesulitan Membaca Siswa Kelas II SD - Agustira Lean Cahya Utami; Ahmad Gawdy Prananosa; Dedy Firduansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine students difficulties in reading ini grade II students at SD Negeri 38 Lubuklinggau, to determine the factors that cause reading difficulties in grade II Students at SD Negeri 38 Lubuklinggau and to find out and to find out the teachers efforts to overcome difficulties in reading in grade II students SD Negeri 38 Lubuklinggau. This type of research used in research is using a qualitative case study approach. The subjects in this study were grade II students at SD Negeri 38 Lubuklinggau. Data collection techniques were 6 students who had difficulty reading. The types of difficulte experienced by students are: Lack of recognition of letters, difficulty reading word for word, difficulty in distinguishing letters, not placing books too close to the eyes, difficulty in reading punctuation, lack of understanding of reading content, lack of eliminating word, lack of memory, difficulty spelling, difficulty pronouncing letters, errors in substituting letters. Factors causing reading difficulties in grade II students at SD Negeri 38 Lubuklinggau are caused by two factor, namely, internal and external factors, internal factors, lack of interest in learning to read, students not attending kingdergarten (TK), intelligence factors that can affect students in reading, external factors, the teacher lacks motivation to students who have difficulty reading, familly factors that play less attention to children who have difficulty reading. Efforts made by the teacher in overcoming the reading difficulties of grade II students at SD Negeri 38 Lubuklinggau are by using interesting and effective learning media, increasing self-confidence, providing motivation, not blaming the conditions experienced by students and providing special remedial reading programs to class students II SD Negeri 38 Lubuklinggau. Keywords: Reading Difficulty Analysis, Class II Students, Elementary School